The role of psychosocial support in the experiences of people living with advanced cancer: A qualitative exploration of patients' perspectives. Issue 3 (21st October 2020) - Newton, Jade C.; O'Connor, Moira; Saunders, Christobel; Moorin, Rachael; Ali, Sayed; Nowak, Anna K.; Halkett, Georgia K. B.
Abstract: Background: People living with advanced cancer experience significant distress and reduced quality of life due to their symptom burden and life‐limiting prognosis. Limited qualitative research has investigated their experiences accessing psychosocial supportive care, and how it meets their needs. Aim: To explore patients' perspectives of the role of psychosocial support in their experiences of living with advanced cancer. Methods: This study used an exploratory qualitative research design and drew upon a social constructionist interpretive framework. Semi‐structured interviews were conducted with 23 participants. Participants were asked about their experiences accessing and using psychosocial support following their diagnosis. Audio‐recorded interviews were transcribed and analysed using deductive thematic analysis. Results: The following six themes can be used to describe participants' experiences with psychosocial support: (1) accessing different types of support, (2) appreciating support, (3) need, (4) difficulties accessing support, (5) knowing about support and (6) asking for support. Sources of psychosocial support included family and friends, health professionals, and psychosocial supportive care services. Not all participants were able to access care that met their needs; barriers included suitability of available support, accessibility and stigma surrounding support use. Conclusion: Participants experienced broad variation in their awareness and access to psychosocial support services to meet their needs. Providers of psychosocial supportive care for advanced cancer patients need to consider service accessibility issues. Future psychosocial interventions targeting people living with advanced cancer should consider these issues during development and implementation.